Dynamics of the Honeybee (Apis mellifera) Gut Microbiota Throughout the Overwintering Period in Canada - Bleau, Naomie (Microorganisms, 2020)
Microbial symbionts inhabiting the honeybee gut (i.e., gut microbiota) are essential for food digestion, immunity, and gut protection of their host. The taxonomic composition of the gut microbiota is dynamic throughout the honeybee life cycle and the foraging season. However, it remains unclear how drastic changes occurring in winter, such as food shortage and cold weather, impact gut microbiota dynamics. The objective of this study was to characterize the gut microbiota of the honeybee during the overwintering period in a northern temperate climate in Canada. The microbiota of nine honeybee colonies was characterized by metataxonomy of 16S rDNA between September 2017 and June 2018. Overall, the results showed that microbiota taxonomic composition experienced major compositional shifts in fall and spring. From September to November, Enterobacteriaceae decreased, while Neisseriaceae increased. From April to June, Orbaceae increased, whereas Rhizobiaceae nearly disappeared. Bacterial diversity of the gut microbiota decreased drastically before and after overwintering, but it remained stable during winter. We conclude that the honeybee gut microbiota is likely to be impacted by the important meteorological and dietary changes that take place before and after the overwintering period. Laboratory trials are needed to determine how the observed variations affect the honeybee health.